What hypertensive patients want to know [and from whom] about their disease: a two-year longitudinal study - Erika R. Cappelletti; Andrea Greco; Alessandro Maloberti; Cristina Giannattasio; Patrizia Steca; Marco D'Addario (BMC, 2020)
Abstract Background This study explored both the evolution of the information needs and the perceived relevance of different health information sources in patients with essential hypertension. It also investigated the relationships between information needs and the perceived relevance of information sources with socio-demographic and clinical variables. Methods Two hundred and two patients with essential arterial hypertension were enrolled in the study and evaluated at baseline and during three follow-ups at 6, 12 and 24 months after baseline. Patients had a mean age of 54.3 years [range 21-78; SD = 10.4], and 43% were women. Repeated measures ANOVA, Bonferroni post hoc tests, and Cochran's Q Test were performed to test differences in variables of interest over time. Results It was observed a significant reduction in all the domains of information needs related to disease management except for pharmacological treatment and risks and complications. At baseline, patients reported receiving health information primarily from specialists, general practitioners, relatives, and television, but the use of these sources decreased over time, even if the decrease was significant only for relatives. Multiple patterns of relationships were found between information needs and the perceived relevance of sources of information and socio-demographics and clinical variables, both at baseline and over time. Conclusions The findings showed a general decrease in both the desire for information and the perceived relevance of different information sources. Hypertensive patients appeared to show little interest in health communication topics as their disease progressed. Understanding patients' information needs and the perceived relevance of different information sources is the first step in implementing tailored communication strategies that can promote patients' self-management skills and optimal clinical outcomes.